Effect of Media Channels, Media Content, Word of Mouth on Negative Consumer Well-Being with Self-Regulation, Fear of Missing Out and Panic Buying as Mediation Variables - Andrew Santo; Sihombing, Sabrina O. (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The widespread phenomenon of panic buying is often influenced by psychological mechanisms involving self regulation, Fear of Missing Out (FoMO), and social influences. This study aims to analyze the impact of self regulation and FoMO on panic buying behavior and the negative effects of both on consumer well-being. The Labubu keychain, a product that went viral on social media, serves as a case study to illustrate this phenomenon. Most consumers feel compelled to make impulsive purchases due to product scarcity exacerbated by FoMO. Based on the theoretical model, self-regulation acts as a mechanism to mitigate the negative effects of FoMO, reducing the likelihood of impulsive purchases. This research also highlights the importance of a deeper understanding of these psychological mechanisms for marketers and policymakers, in order to promote more thoughtful and sustainable purchasing behaviors.